Inflammatory targeted nanoplatform incorporated with antioxidative nano iron oxide to attenuate ulcerative colitis progression - Haojun Chen; Wei Sun; Can Li; Qiuyang Wang; Xucai Wang; Yingjie Du; Wenbo Chen; Min Wang; Caoxing Huang; Rong Wang (iScience)
Summary: Antioxidative nanomaterials with reactive oxygen species (ROS) scavenging capabilities hold promise for the treatment of ulcerative colitis (UC). However, their clinical application is limited by rapid diffusion, susceptibility to inactivation, and insufficient targeting of inflammatory sites. This study focuses on developing a nanoplatform by integrating iron oxide nanoparticles (IONPs) into zeolitic imidazolate frameworks-8 (ZIF-8), termed as ZIF-8@IONPs. ZIF-8@IONPs exhibited good biocompatibility and effective ROS scavenging capabilities in RAW 264.7 cells. To enhance inflammatory targeting, HA@ZIF-8@IONPs were generated through hyaluronic acid (HA) surface modification. HA@ZIF-8@IONPs effectively reduced damage to intestinal tissues in the UC mouse model. Mechanistic revealed that HA@ZIF-8@IONPs exhibited antioxidant and anti-inflammatory activities by eliminating endogenous ROS, activating the Nrf2 signaling pathway, and inhibiting the NF-κB signaling pathway. This study highlights the nanoplatform’s potential as a promising candidate for UC treatment due to its great targeting of inflammatory microenvironments and efficient ROS scavenging.